An Evaluation of the Curve of Spee in the Maxilla and Mandible of Human Permanent Healthy Dentitions: A Cross Sectional Analytical Study in a Group of Nepalese Population - Dhital, S; Ghimire, B; Basnet, BB; Shrestha, B (Journal of Nepalese Prosthodontic Society, 2023)
Introduction: Familiarity with the typical measurements of the maxillary and mandibular curves of Spee can assist clinicians in formulating sagittal plane occlusion and proves beneficial in delivering prosthetic rehabilitation for patients with occlusal derangement. The objective of this study is to evaluate and compare the radius and depth of the Spee curve in the maxillary and mandibular arches among both male and female individuals within young Nepalese population.Materials and Methods: The study comprised 21 men and 21 women aged between 18 and 30 years. Alginate impressions were made for both the maxillary and mandibular arches and dental stone casts were subsequently created. Digital images of the right side of maxillary and mandibular dental casts were captured using a digital camera and subsequently transferred to a computer. The tips of the distal cusps of molars, premolars, and canines in both the maxillary and mandibular arches were identified. Utilizing the computer software (Corel DRAW), the radius and depth of the Spee curve were measured based on the digital photographs of the dental casts.Results: The results indicated a substantial difference in the depth of the Spee curve between the mandibular and maxillary arches (p